2019
DOI: 10.1158/1078-0432.ccr-18-3661
|View full text |Cite
|
Sign up to set email alerts
|

Association of Systemic Inflammation Index and Body Mass Index with Survival in Patients with Renal Cell Cancer Treated with Nivolumab

Abstract: Purpose: Inflammation indexes and body mass index (BMI) are easily evaluated, predict survival, and are potentially modifiable. We evaluated the potential association of inflammatory indexes and BMI with the clinical outcome of patients with renal cell carcinoma (RCC) undergoing immune checkpoint inhibitor therapy.Experimental Design: A prospective cohort of patients with metastatic RCC treated with nivolumab enrolled in the Italian Expanded Access Program from July 2015 through April 2016 was examined. Refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
151
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(157 citation statements)
references
References 34 publications
(36 reference statements)
3
151
3
Order By: Relevance
“…BMI is widely used for relating weight to height, defining body size, and indicating nutritional status. In addition, a lower BMI is associated with increased mortality risk [21][22][23][24]. Our previous clinical study demonstrated that NSCLC patients with sarcopenia exhibit a significantly shorter median PFS following ICI treatment compared to that of non-sarcopenia patients [25].…”
Section: Discussionmentioning
confidence: 99%
“…BMI is widely used for relating weight to height, defining body size, and indicating nutritional status. In addition, a lower BMI is associated with increased mortality risk [21][22][23][24]. Our previous clinical study demonstrated that NSCLC patients with sarcopenia exhibit a significantly shorter median PFS following ICI treatment compared to that of non-sarcopenia patients [25].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic immune‐inflammation index (SII) is a novel inflammatory marker which combines NLR and platelet is an independent risk factor for the development of solid cancer . Higher SII was independently associated with worse outcomes for metastatic renal cell carcinoma (RCC) patients treated with nivolumab . However, rare studies reported whether SII is associated with the prognosis of NSCLC patients treated with ICIs.…”
Section: Introductionmentioning
confidence: 99%
“…It is thus expected that the continuing increase of therapeutic options (including ICIs as well as targeted agents) will lead to further improvement in the prognosis for patients with mRCC in the coming years. At the same time, we expect that a more personalized therapeutic strategy will be established for older patients that is based on key molecules identified through gene sequencing in addition to conventional predictive factors for prognosis and agent efficacy (22,23) as older patients tend to have more comorbidities than younger ones.…”
Section: Discussionmentioning
confidence: 99%